Active and reactive power management of grid connected photovoltaic system - Ameerul A. J. Jeman; Naeem M. S. Hannoon; Nabil Hidayat; Mohamed.M.H. Adam; Ismail Musirin; Vijayakumar. V (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
Voltage-source converter (VSC) topology is widely used for grid interfacing of distributed generation (DG) systems such as the photovoltaic system (PV). Since the operation of the VSC is essential to ensure quality of active and reactive power injected to the grid, a control approach is needed to deal with the uncertainties in the grid such as faults. This paper presents a non-linear controller design for a three-phase voltage source converter (VSC). The dynamic variables adopted for the VSC are the instantaneous real and reactive power components. The control approach that interface the VSC between the PV system and the grid are subjected to the current-voltage based. PV system injects active power to the grid and local load while utility grid monitors the power compensation of load reactive power. The proposed non-linear control strategy is implemented for the VSC to ensure fast error tracking and finite convergence time. The adaptive nature of the proposed non-linear control provides more robustness, less sluggish fault recovery compared to conventional PI control. The comprehensive numerical model is demonstrated in MATLAB script environment with power system disturbances such as faults in the grid. The simulation of proposed system is being carried out in MATLAB/SIMULINK environment to validate the control scheme. The proposed control system regulates the VSC ac side real and reactive power component and the dc side voltage.